2010
DOI: 10.1089/fpd.2010.0567
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Different Recall Periods on Estimates of Acute Gastroenteritis in the United States, FoodNet Population Survey 2006–2007

Abstract: First asking respondents about a 7-day recall period did not affect the prevalence of acute gastroenteritis reported for a 1-month recall period. Recall period length did, however, have a major impact on estimates of acute gastroenteritis. Retrospective studies using different recall periods may not be comparable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
29
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 11 publications
1
29
0
2
Order By: Relevance
“…Overall, 6% reported having experienced an acute diarrheal illness at some point during the 4 weeks preceding the interview (overall annualized rate, 0.72 episodes per person-year; 15-24, 1.1 episodes per person-year; 25-44, 1.7 episodes per person-year; 45-64, 1.2 episodes per person-year). A follow-up survey where 3,568 respondents (median age 51) were asked at random about illness in the previous 7 days or previous month found that recall bias had an important eff ect on estimates of acute gastrointestinal illness ( 10 ). Using a 7-day exposure window, the estimated incidence of acute diarrhea was 1.6 episodes per person-year, compared with 0.9 episodes per person-year if asked about illness within the preceding month.…”
Section: Recommendationmentioning
confidence: 99%
“…Overall, 6% reported having experienced an acute diarrheal illness at some point during the 4 weeks preceding the interview (overall annualized rate, 0.72 episodes per person-year; 15-24, 1.1 episodes per person-year; 25-44, 1.7 episodes per person-year; 45-64, 1.2 episodes per person-year). A follow-up survey where 3,568 respondents (median age 51) were asked at random about illness in the previous 7 days or previous month found that recall bias had an important eff ect on estimates of acute gastrointestinal illness ( 10 ). Using a 7-day exposure window, the estimated incidence of acute diarrhea was 1.6 episodes per person-year, compared with 0.9 episodes per person-year if asked about illness within the preceding month.…”
Section: Recommendationmentioning
confidence: 99%
“…The methodology for community surveys has improved over the years and a common case definition was established to ensure international comparability [1][2][3]. These efforts resulted in cross-sectional studies for estimates for the burden of AGI from various countries [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] and additionally a few population-based cohort studies [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…等归纳总结了美国多个监测系统关于食源性疾病的监测资料,估计美 国每年约有 7600 万例食源性疾病病例, 其中约 32.5 万人入院治疗, 5000 人死亡; 急性胃肠炎病人中 25%~ 30%是食源性导致的 [4] ;2011 年美国 CDC 根据主动和被动监测系统数据分析,美国每年约有 4800 万例食 源性疾病发生,32 万人住院,3000 人死亡,其中 58%由瓦克病毒引起,其次为沙门氏菌 11%,产气荚膜 梭菌 10% [5,6] 。 在英国,食源性疾病每年导致 236 万余人发病,2 万余人住院,718 人死亡 [4] 。约有 1/5 的肠道感染病 是经食物传播的 [7] ;1996-2000 年英格兰和威尔士年均食源性疾病发病 170 余万例,住院约 2.2 万人,死 亡 687 人,其中最主要的发病和死亡的致病因素为弯曲杆菌和沙门菌 [8] 。澳大利亚报道认为 32%的肠道感 染病是食源性的 [9] ;2010 年,澳大利亚 OzFoodNet 监测网报告 3 万余人患食源性感染性疾病,其中感染率 第一的是弯曲杆菌,其次是沙门菌 [10] [20] 。以 Food Net 数据为基础,估算美国食源性疾病 负担,急性胃肠炎的食源性比例为 25%,其中 20%归因于已知的病原体 [5] 。加拿大和澳大利亚也进行了类 似的研究,结果表明,急性胃肠炎发病率为 1.3 次/人年和 0.92 次/人年,估计每年约发生 1100 万例和 540 万例食源性疾病。 英国和荷兰采用了前瞻性巢式病例对照研究。2008-2009 年,英国开展了包括急性胃肠炎电话调查和 前瞻性人群急性胃肠炎队列研究。研究结果表明,社区急性胃肠炎发病率为 0.274 次/人年 [21,22] 。荷兰人群 中急性胃肠炎发病率分别为 0.283 次/人年。Havelaar AH 等研究表明弯曲菌和大肠杆菌 O157 对荷兰人群每 年造成的平均健康负担估计有 1400 DALYs 和 116 DALYs [23] ,WHO 的报告中,腹泻的伤残系数由原来的 0.04 调整为 0.109,这意味着全球对腹泻病的严重程度的估计比之前有所提高。 3.4 中国疾病负担研究 由于我国食源性疾病主动监测工作开展时间尚短,该领域面临覆盖面不足、技术 条件落后、专业人员缺乏等诸多问题,也尚未建立完善的临床病例食源性病原体监测机制,食源性疾病的 真实负担尚不明确。估计食源性疾病负担的全国性人群调查还未开展,大规模的食源性疾病对我国造成的 疾病负担还未见报道。但是,部分地区已经开展了腹泻的人群调查,报道了医院腹泻或肠道门诊的腹泻患 者粪便/肛拭的检测结果 [24][25][26][27][28] 。2012-2011 年,食品安全风险评估中心与上海、江苏、浙江、江西、广西、 四川 6 个省(区、市)的疾病预防控制中心合作,开展人群急性胃肠炎横断面入户调查。结果表明,急性 胃肠炎加权月患病率为 4.2%,发病率为 0.56 次/人年,这些为我国食源性疾病负担的研究提供了数据基础 [29,30] …”
unclassified